Langerhan’s cell histiocytosis with oral manifestation in a 3-year-old child: a case report (Research, Society and Development, 2021)
Langerhans cell histiocytosis (LCH) is a disorder that may affect the bones, skin, liver, lung, and hematopoietic and neuroendocrine systems. This condition may manifest as a single lesion, multiple lesions, or as a disseminated and potentially fatal disease. We aim to report a case of a 3-year-old child with LCH in the mandible, sharing with the readers the challenging process of this diagnosis. A three-year-old male patient with persistent swelling in the right submandibular region was referred to the Department of Pediatrics of the Erasto Gaertner Hospital for an evaluation. Initial physical exam revealed a diffuse flaccid swelling occupying the entire right mandibular ramus, from the angle to the preauricular region and CT scan showed an osteolytic lesion with erosion of the internal and external cortices of the mandible and an extension to soft tissues that displaced the masseter muscle. Immunohistochemical analysis confirmed the diagnosis of Langerhans cell histiocytosis through positive tests for CD1a, CD68, S-100, and Vimentin. The treatment proposed was a combination of Vinblastine 6 mg/m3 for 6 weeks and Prednisone 40mg for 4 weeks.The differential diagnosis included pathologies such as rhabdomyosarcoma, Ewing's sarcoma, and, less likely, osteosarcoma and central giant cell granuloma.